Defining the Outcome of Ventricular Tachycardia Ablation: Timing and Value of Programmed Ventricular Stimulation. (March 2018) - Oloriz, Teresa; Baratto, Francesca; Trevisi, Nicola; Barbaro, Melania; Bisceglia, Caterina; D'Angelo, Giuseppe; Yamase, Miki; Paglino, Gabriele; Radinovic, Andrea; Della Bella, Paolo
Abstract : Background: Catheter ablation of ventricular tachycardia (VT) is effective to prevent arrhythmia episode–related implantable cardioverter defibrillator shocks. However, recurrences in noninducible patients at programmed ventricular stimulation (PVS) are substantial. Methods and Results: From May 2013 to September 2015, 218 PVSs were performed 6 days (5–7) after ablation (186 noninvasive programmed stimulations and 32 invasive PVS) in 210 consecutive patients (ischemic, 48%; median left ventricular ejection fraction, 37%; syncope, 35% with trauma associated 6%), while patients were awake and under β-blocker therapy. After ablation, implantable cardioverter defibrillators were programmed according to noninvasive programmed stimulations results (class A—noninducible; class B—nondocumented inducible VT; and class C—documented inducible VT), with high and delayed VT detection intervals. Concordance between PVS end procedure and PVS day 6 was 67%. Positive predictive value and negative predictive value were higher for PVS day 6 (53% and 88% versus 43% and 71%). Ischemic and patients with preserved ejection fraction showed the highest negative predictive value (91% and 96%). Among 46 of 174 (26%) noninducible patients at PVS end procedure, but inducible at day 6, 59% had VT recurrence at 1-year follow-up; recurrences were 9% when both studies were noninducible. There were no inappropriate shocks; incidence of syncope was 3%; and none was harmful. The rate of appropriate shocks per patient per month according to noninvasive programmed stimulations results was significantly reduced, comparing the month before and after ablation (class A: 2 [0.75–4] versus 0; class B: 2 [1–4] versus 0; class C: 2 [1–4] versus 0; P <0.001). Conclusions: PVS at day 6 predicts VT recurrence more accurately allowing to identify patients who might benefit from a redo ablation and addressing implantable cardioverter defibrillator programming. Abstract : Supplemental Digital Content is available in the text.